(untitled) (SAARC Journal of Agriculture, 2021)
An experiment was carried out to investigate the performances with 1080 male Cobb-500 broiler chicks using different levels of a microbial phytase in plantbased diet. Six dietary treatments were formulated as follows; the first 3 diets were balanced with Ca and Av. P according to the recommendation of Cobb-500 served as basal diet without phytase enzyme (T1), basal diet with 100g phytase ton-1 feed (T2) and basal diet with 200g phytase ton-1 feed (T3), while the last 3 diets were deficient in Ca and Av. P and containing no phytase enzyme (T4), diet with 100g phytase/ton feed (T5) and diet with 200g phytase ton-1 feed (T6). All 6 treatments were replicated 6 times. Body weight, feed consumption and mortality of broilers were recorded weekly. The highest body weight was found in T3 with 200g phytase ton-1 feed with recommended Ca and Av. P level in the diet, followed by T6 with 200g phytase/ton feed with deficient in Ca and Av. P level in the diet (P<0.05). The lowest weight was found in T1 without phytase with recommended Ca and Av. P level in the diet. The feed consumption, feed conversion ratio and mortality of the birds during 35 days of experimental period did not differ significantly (P<0.05). The meat yield characteristics at 35 days of age were non-significant among different treatments (P>0.05). Significantly lower value of total ash (%), Ca (%) and total P (%) of tibia was found in control group (T1) and T4. The results of this experiment revealed that phytase supplementation at 200g ton-1 of feed improved broiler performances at either recommended or deficient level of Ca and Av. P. SAARC J. Agric., 19(1): 211-222 (2021)